Extraordinary adventures [large type] : a novel - Wallace, Daniel, 1959- (Thorndike Press, a part of Gale, Cengage Learning, 2017)
Edsel Bronfman works as a junior executive shipping clerk and spends his free time with his mother. Then he gets a call telling him that he's won a free weekend at a beachfront condo in Florida. There's a catch: the offer is intended for a couple. Jolted into motion, Bronfman sets out to find a companion for his weekend getaway.